Combined Photothermal and Ionizing Radiation Sensitization of Triple-Negative Breast Cancer Using Triangular Silver Nanoparticles - Sears J (Dove Medical Press, 2021)
James Sears,1 Jessica Swanner,1 Cale D Fahrenholtz,1,2 Christina Snyder,1 Monica Rohde,1 Nicole Levi-Polyachenko,3,4 Ravi Singh1,4 1Department of Cancer Biology, Wake Forest School of Medicine, Winston-Salem, NC, USA; 2Department of Basic Pharmaceutical Sciences, Fred Wilson School of Pharmacy, High Point University, High Point, NC, 27268, USA; 3Department of Plastic Surgery and Reconstructive Medicine, Wake Forest School of Medicine, Winston-Salem, NC, USA; 4Comprehensive Cancer Center, Wake Forest Baptist Medical Center, Winston-Salem, NC, USACorrespondence: Ravi SinghDepartment of Cancer Biology, Wake Forest School of Medicine, Medical Center Blvd., Winston-Salem, NC, 27157, USATel +336-713-4434Fax +336-716-0255Email rasingh@wakehealth.eduBackground: Ionizing radiation (IR) is commonly used in triple-negative breast cancer (TNBC) treatment regimens. However, off-target toxicity affecting normal tissue and grueling treatment regimens remain major limitations. Hyperthermia is one of the greatest IR sensitizers, but only if heat is administered simultaneously or immediately prior to ionizing radiation. Difficulty in co-localizing ionizing radiation (IR) in rapid succession with hyperthermia, and confining treatment to the tumor have hindered widespread clinical adoption of combined thermoradiation treatment. Metal nanoparticle-based approaches to IR sensitization and photothermal heat generation may aid in overcoming these issues and improve treatment specificity.Methods: We assessed the potential to selectively treat MDA-MB-231 TNBC cells without affecting non-malignant MCF-10A breast cells using a multimodal approach based upon combined photothermal therapy, IR sensitization, and specific cytotoxicity using triangular silver nanoparticles (TAgNPs) with peak absorbance in the near-infrared light (NIR) spectrum.Results: We found that TAgNP-mediated photothermal therapy and radiosensitization offer a high degree of specificity for treatment of TNBC without affecting non-malignant mammary epithelial cells.Discussion: If given at a high enough dose, IR, heat, or TAgNPs alone could be sufficient for tumor treatment. However, when the dose of one or all of these modalities increases, off-target effects also increase. The challenge lies in identifying the minimal doses of each individual treatment such that when combined they provide maximum selectivity for treatment of TNBC cells with minimum off-target effects on non-malignant breast cells. Our results provide proof of concept that this combination is highly selective for TNBC cells while sparing non-malignant mammary epithelial cells. This treatment would be particularly important for patients undergoing breast conservation therapy and for treatment of invasive tumor margins near the periphery where each individual treatment might be at a sub-therapeutic level.Keywords: radiation sensitizer, hyperthermia, nanoparticle, cancer, laser